2017
DOI: 10.1186/s12879-017-2709-x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of HIV-1 drug resistance in patients on a standard thymidine analogue-based first line antiretroviral therapy after virological failure: implications for the activity of next-line regimens from a longitudinal study in Mozambique

Abstract: BackgroundWe describe the accumulation of HIV-1 drug resistance and its effect on the activity of next-line components in patients with virological failure (HIV-1 RNA >1000 copies/mL) after 1 year (t1) of first-line antiretroviral therapy (ART) not switching to second-line drugs for one additional year (t2) in low-middle income countries (LMIC).Methods and resultsWe selected 48 patients from the DREAM cohort (Maputo, Mozambique); their median pre-ART CD4+ cell count was 165 cells/μl. At t1 patients were receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…This could be because of possible cross resistance mutations in this subgroup of patients as suggested previously [25, 26]. In Mozambique it was shown that resistance mutations were a common cause of virological failure on first line ARTs, the prevalence of which kept on increasing with time on ART [27]. This suggests that in settings like ours where switching to second line ART is not routinely guided by resistance testing, a possible selection and accumulation of drug resistant strains could possibly lead into early failure of second line ART regimen [26, 28], though the time on second line ART was not statistically different in our study between those failing virologicaly and their successful counter parts (6 months vs. 9 months, p = 0.065).…”
Section: Discussionmentioning
confidence: 78%
“…This could be because of possible cross resistance mutations in this subgroup of patients as suggested previously [25, 26]. In Mozambique it was shown that resistance mutations were a common cause of virological failure on first line ARTs, the prevalence of which kept on increasing with time on ART [27]. This suggests that in settings like ours where switching to second line ART is not routinely guided by resistance testing, a possible selection and accumulation of drug resistant strains could possibly lead into early failure of second line ART regimen [26, 28], though the time on second line ART was not statistically different in our study between those failing virologicaly and their successful counter parts (6 months vs. 9 months, p = 0.065).…”
Section: Discussionmentioning
confidence: 78%
“…Detection of this mutation could be associated with acquisition with already HIV drug resistant strains from infected individuals on either AZT or D4T treatment [31, 32]. Nevertheless, K103 N, V108I, V179E, and Y181C, NNRTI mutations that confer resistance to Efavirenz (EFV) and Nevirapine (NVP) were also detected [28, 33]. Based on the ART drug combinations, these mutations could similarly be associated with the transmission of resistant viral strains from already known populations on treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the G208R and T210K mutants, the total negative charge at this interface is reduced, resulting in less lattice destabilizing repulsion force. A hyperstable capsid deviating from a fine balance could have deleterious effects for the virus, which may explain why these mutations are rarely seen in patient samples [26].…”
Section: Resultsmentioning
confidence: 99%